Introduction - Bruck, Mozahir Salomão; Tárcia, Lorena; Gambarato, Renira Rampazzo (Brazilian journalism research, 2019)
Invited Editors: Mozahir Salomão Bruck, Pontifícia Universidade Católica de Minas Gerais, Brazil Lorena Tárcia, Centro Universitário de Belo Horizonte, Brazil Renira Rampazzo Gambarato, Jönköping University, Sweden